Resolusi Degradasi Pendidikan Desa Banyusidi melalui Program “Bhumi Literasi” Berbasis Digital - Wastiana; Siti Imronah; Winasti Rahma Diani (Universitas Muhammadiyah Malang, 2024)
Purpose – The aim of the “Bhumi Literacy” program is to overcome the decline in education in Banyusidi Village and reinvigorate the literacy spirit of the target participants. Methodology – One of the crucial problems is the degradation of education as evidenced by the high school dropout rate and the decline in literacy. To overcome this, the Ormawa Student Association of the Indonesian Language and Literature Education Study Program through the Student Organization Capacity Strengthening Program (PPK Ormawa) carries out community empowerment activities with the